Componentes genéticos para ganho em peso de bovinos Nelore sob diferentes cargas de ecto e endoparasitos - Larissa Kretli Winkelstroter (2017)
Parasites play an important role in the evolution of the traits of their hosts. These hosts can protect themselves through two mechanisms of defense, resistance and tolerance. Resistance is widely studied in plants and animals. However, tolerance is rarely addressed and characterized. Tolerance evaluation is commonly performed by analyzing the regression coefficient of performance as a function of the parasitic load. Thus, this work was developed with the purpose of verifying the variation of the genetic components of ecto and endoparasites tolerance in beef cattle under natural infestation. Average daily gain and endo and ectoparasite infestations data of 1.318 animals were used to evaluate the effect of parasitic load on genetic parameters of the average daily gain through random regression. Genetic parameters, heritability and additive genetic variance, were estimated for the average daily gain as a function of the increase in parasite count. An increase in these genetic parameters was observed as the count increased. The genetic value of the animals that had significant contribution in the genetic composition of the herd was demonstrated as a reaction norm plot. There was an increase in the variance between these values as the animals presented higher parasite load, most of animals with progeny in the herd presented negative values for parasite tolerance. The average daily gain of cattle under different loads of ecto and endoparasites is a trait influenced by the genetic composition of the animals. It is possible to have genetic gain for average daily gain under different parasitic loads. Infestation by parasites should be considered when selecting the animals, once there is variation of the genetic values as a function of parasite load.